Phenolic Extract from Sonchus oleraceus L. Protects Diabetes‐related Liver Injury in Rats through TLR4/NF‐κB Signaling Pathway. Issue 1 (2nd November 2019) - Chen, Lei; Fan, Xiaoyun; Lin, Xiujun; Qian, Liu; Zengin, Gokhan; Delmas, Dominique; Paoli, Paolo; Teng, Hui; Xiao, Jianbo
Abstract : Sonchus oleraceus Linn. is of great interest in scientific platform because it exhibits significant biological activities. This study investigated the liver protective effects and mechanism of phenolic extract from S. oleraceus (SOL) on Streptozotocin (STZ)‐induced diabetic rats. SOL significantly increased both superoxide dismutase activity and glutathione level, while causing a reduction of malondialdehyde level in the liver. Moreover, SOL ameliorates STZ‐induced liver function and pathological damages. Diabetic rats fed with S. oleraceus daily for 6 weeks showed significantly decreased levels of tumor necrosis factor alpha and interleukin‐1 β in the liver. Sonchus oleraceus decreased the expression levels of MyD88, TGF‐ β, and Toll‐Like Receptor (TLR)4 in the liver of diabetic rats. In conclusion, SOL possesses anti‐inflammatory activity and suppresses the TLR4/nuclear factor kappa B (NF‐κB) p65 signaling pathway.